An analysis of cooperative compliance programmes : legal and institutional aspects with a focus on application in less developed countries - Majdanska, Alicja (Doctoral series, 2021)
The book provides an insightful discussion on the design of a cooperative compliance programme, based on the analysis of legal principles and State aid rules.